Pengembangan Fasilitas Share Screen Pada Media Webex untuk Meningkatkan Kemampuan Menulis Teks Report Siswa - Kartinah, Atin (Jurnal Nispatti, 2025)
This study investigated the use of sharing screen facility on Cisco Webex media in teaching writing proses on Report Text of IXC students SMPN 2 Garut. It’s an action research study used systematically method which starts from planning, doing, observing, and evaluating (self-evaluating), and reflecting. The participants included 30 of 9C students of junior high school 2 in Garut. This study examined two types of data. The first data were texts written by students in the first, the second and the third cycle. The second data were the students’ opinion, which was gathered through an interview after each cycle. This study found that generally learning activities used share screen facility on Cisco Webex media impoved. It’s showed on the second and third draft of sudents’ text are better with more improving ideas and better sentence structures from the first draft. At the end of the writing activities with facility of share screen on media Cisco Webex influence on students writing abilities on Report text. It is also found this effectiveness is supported by the findings from the interview: the students found the learning activities both enjoyable and beneficial.